Development of polylactide and polyethylene vinyl acetate blends for the manufacture of vaginal rings - McConville, Christopher; Major, Ian; Friend, David; Clark, Meredith; Woolfson, A; Malcolm, R (Wiley, 2012)
Vaginal rings are currently being investigated for delivery of HIV microbicides. However, vaginal rings are currently manufactured form hydrophobic polymers such as silicone elastomer and polyethylene vinyl acetate (PEVA), which do not permit release of hydrophilic microbicides such as the nucleotide reverse transcriptase inhibitor tenofovir. Biodegradable polymers such as polylactide (PLA) may help increase release rates by controlling polymer degradation rather than diffusion of the drug through the polymer. However, biodegradable polymers have limited flexibility making them unsuitable for use in the manufacture of vaginal rings. This study demonstrates that by blending PLA and PEVA together it is possible to achieve a blend that has flexibility similar to native PEVA but also allows for the release of tenofovir.